Pengaruh Kultur Bakteri Pada Proses Biosementasi Tanah Laterit Terhadap Nilai CBR: The Influence Of Bacterial Culture On The Soil Laterite Biosementation Process On CBR Value - Andi Marini Indriani; Gunaedy Utomo; Nurul Fitriyani (Media Ilmiah Teknik Sipil, 2023)
Lateritic soils have a high rate of weathering and non-uniform shrinkage. So this land is not good for construction work. Biocementation is a method of soil improvement by using the ability of bacteria that have lived in the soil to do the MCIP (Microbial-induced Calcite Precipitation) process which is obtained from the bacterium Bacillus Subtilis. This biocementation stabilization can increase the strength of the soil by adding Bacillus Subtilis bacteria as an additive to stabilize the soil. The test was carried out to determine changes in the mechanical properties of CBR Laboratory soil, by mixing 3% bacteria into the soil to be stabilized. The results of testing the CBR value of the Soaked Laboratory with one day of culture increased 4.8-fold at the 28-day curing period and increasing the CBR value of the Soaked Laboratory of three-day culture increased up to 4.9 times the CBR value before stabilization, which was 19.5%. The results of the study with stabilization using bacteria variation of 3% one-day culture increased up to 95% and increased up to 96% in three-day culture. So that it can be used as a soil material for road foundations in class B.